Disability in industrial Britain: A cultural and literary history of impairment in the coal industry, 1880-1948 - Bohata, Kirsti (Manchester University Press, 2019)
Coalmining was a notoriously dangerous industry and many of its workers experienced injury and disease. However, the experiences of the many disabled people within Britain's most dangerous industry have gone largely unrecognised by historians. This book examines the British coal industry through the lens of disability, using an interdisciplinary approach to examine the lives of disabled miners and their families. The book considers the coal industry at a time when it was one of Britain's most important industries, and follows it through a period of growth up to the First World War, through strikes, depression and wartime, and into an era of decline. During this time, the statutory provision for disabled people changed considerably, most notably with the first programme of state compensation for workplace injury. And yet disabled people remained a constant presence in the industry as many disabled miners continued their jobs or took up 'light work'. The burgeoning coalfields literature used images of disability on a frequent basis and disabled characters were used to represent the human toll of the industry. A diverse range of sources are used to examine the economic, social, political and cultural impact of disability in the coal industry, looking beyond formal coal company and union records to include autobiographies, novels and oral testimony. It argues that, far from being excluded entirely from British industry, disability and disabled people were central to its development. The book will appeal to students and academics interested in disability history, disability studies, social and cultural history, and representations of disability in literature.